2006
DOI: 10.1177/154405910608500111
|View full text |Cite
|
Sign up to set email alerts
|

Pilocarpine-induced Salivation and Thirst in Conscious Rats

Abstract: The muscarinic receptor agonist pilocarpine is widely used as a sialogogue. It has been well-established that it also induces water intake in animals. However, the mechanisms underlying the relationships between these events are unknown. To address this problem, we examined water intake and parotid salivary secretion in conscious rats. Intraperitoneally injected pilocarpine increased both water intake and salivary secretion. Intracerebroventricularly injected pilocarpine also induced water intake, but not sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Similar to pirenzepine, small doses of 4‐DAMP may block M 1 and/or M 3 receptors located periventricularly that are involved in the dipsogenic response and high doses are needed to block M 1 and/or M 3 receptors involved in pilocarpine‐induced salivation and pressor responses that are located far from the ventricles. A previous study ( Sato et al ., 2006 ) also showed that a small dose of i.c.v. atropine is effective at blocking i.p.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Similar to pirenzepine, small doses of 4‐DAMP may block M 1 and/or M 3 receptors located periventricularly that are involved in the dipsogenic response and high doses are needed to block M 1 and/or M 3 receptors involved in pilocarpine‐induced salivation and pressor responses that are located far from the ventricles. A previous study ( Sato et al ., 2006 ) also showed that a small dose of i.c.v. atropine is effective at blocking i.p.…”
Section: Discussionmentioning
confidence: 84%
“…However, pirenzepine reduced pilocarpine‐induced pressor response only at the dose of 100 nmol, suggesting that central M 1 receptors activated by peripheral pilocarpine to produce dipsogenic responses are not the same as those involved in pressor responses and that they may be located in different central areas. Small doses of pirenzepine may block M 1 receptors localized more periventricularly or more specifically in circumventricular organs, such as the subfornical organ, an area suggested to be activated by pilocarpine to induce water intake in a previous study ( Sato et al ., 2006 ). High doses of pirenzepine are needed to reach areas that are not periventricular, that is, areas that are deeper in the central neural parenchyma and that are activated by pilocarpine to produce pressor responses.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…To induce this thirst sensation, it is important to activate neurons in the circumventricular organs (CVOs), including the organum vasculosum of the lamina terminalis (OVLT) and the subfornical organ (SFO), and the hypothalamus, which are referred to as the dipsogenic center. Oral dryness, which comprises a feeling of dryness in the oral cavity, is produced by a decrease in salivary secretion [3], [4], [5] and is distinguished from thirst sensation [6], [7], [8], [9]. In the present review, thirst sensation and oral dryness after alcohol drinking or administration are differentiated.…”
Section: Introductionmentioning
confidence: 99%